Nd:YAG 레이저 후낭절개술 후 유리체탈출에 의해 발생한 동공차단 및 안압상승 - 강경민, 김종진, 이준훈, 신재필Kyoung Min Kang MD Jong Jin Kim MD Jun Hun Lee MD Jae Pil Shin MD PhD (Daihan angwa haghoi jabji, 2013)
목적: 후발백내장 환자에서 Nd:YAG 레이저 후낭절개술을 시행한 후 유리체탈출에 의한 동공차단 및 안압상승을 보이는 1예를 경험하였기에 이를 보고하고자 한다. 증례요약: 70세 남자 환자가 1일 전부터 시작된 좌안의 시력저하 및 통증을 주소로 내원하였다. 환자는 개인 안과에서 2일 전 좌안의Nd:YAG 레이저 후낭절개술을 시행 받았다. 내원 당시 최대교정시력은 우안 0.63, 좌안 안전수지 60 cm였고, 안압은 우안 14 mmHg,좌안 64 mmHg였다. 세극등현미경 검사상 좌안의 각막부종과 전방 내에 동공을 완전히 막고 있는 탈출된 유리체가 보였고 홍채볼록과함께 전방각은 폐쇄되어 있었다. 동공차단으로 인한 급성안압상승으로 진단하고 홍채절개술을 시행하였다. 시술 3일 후 좌안의 최대교정시력은 0.2로 호전되었고 안압은 11 mmHg로 정상화되었다. 결론: 후방인공수정체를 삽입한 환자에서 Nd:YAG 레이저 후낭절개술을 시행한 후 유리체탈출에 의한 동공차단 및 안압상승은 아직국내 보고가 없는 드문 합병증이며 레이저 홍채절개술이 효과적인 치료라고 생각한다. Purpose: To report a case of pupillary block and increased intraocular pressure caused by vitreous prolapse after Nd:YAG laser posterior capsulotomy. Case summary: A 70-year-old male visited the hospital for decreasing visual acuity and ocular pain in the left eye. Two days earlier, he had undergone Nd:YAG laser posterior capsulotomy in the left eye. Best corrected visual acuity (BCVA)was 0.63 in the right eye and FC 60 cm in the left eye. Intraocular pressure (IOP) was 14 mm Hg in the right eye and 64 mm Hg in the left eye. Slit-lamp examination revealed diffuse corneal stromal edema and iris bombe with vitreous prolapse in the anterior chamber. Gonioscopy confirmed a closed angle. Pupillary block and increased intraocular pressure were diagnosed. A Nd:YAG laser iridotomy was performed. Three days after the iridotomy, BCVA was 0.2 and IOP was 11 mm Hg in the treated eye. Slit-lamp examination revealed reduced vitreous prolapse in the anterior chamber. Conclusions: This is the first report of pupillary block and increased IOP caused by vitreous prolapse after Nd:YAG laser posterior capsulotomy in Korea. Physicians should be aware that pupillary block could be caused by prolapsed vitreous after Nd:YAG laser posterior capsulotomy and Nd:YAG laser iridotomy could be performed effectively in such cases. KCI Citation Count: 1